VARIETIES OF MATHEMATICAL PROSE - Bagchi, Atish; Wells, Charles (PRIMUS : problems, resources, and issues in mathematics undergraduate studies, 1998)
This article begins the development of a taxonomy of mathematical prose, describing the precise function and meaning of specific types of mathematical exposition. It further discusses the merits and demerits of a style of mathematical writing that labels each passage according to its function as described in the taxonomy.